2006
DOI: 10.1002/jmv.20591
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor induction by rhinovirus infection

Abstract: Vascular participation manifested by a runny nose (rhinorrhea) is a prominent feature of the acute consequences of rhinovirus infection. Vascular endothelial growth factor (VEGF) is an angiogenic factor that also induces potent increases in vascular permeability; it is a candidate mediator of rhinorrhea in response to rhinovirus infection as well as contributing to enhanced vascular leakage in rhinovirus-linked asthma exacerbations. It has been shown that rhinovirus induces significant increases in both VEGF p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 41 publications
1
15
1
2
Order By: Relevance
“…Levels of VEGF in nasal secretions were significantly higher at the time of peak symptoms compared with either samples obtained 4 weeks after symptom resolution from the same subjects or levels in nasal secretions of healthy asymptomatic subjects. These data contrast with those of De Silva et al, 28 who found no significant increase in VEGF protein levels in nasal aspirates from patients with confirmed HRV infections compared with noninfected control subjects but agree with the findings of a significant increase in VEGF protein levels in nasopharyngeal secretions of 9 children during asthma exacerbations associated with the presence of HRV compared with levels in the same subjects at baseline. 27 We extended these observations by demonstrating that the levels of VEGF in nasal secretions correlate with viral peak viral titers (r 5 0.35, P 5 .03) and with IP-10 protein levels (r 5 0.70, P < .001).…”
Section: Discussioncontrasting
confidence: 78%
“…Levels of VEGF in nasal secretions were significantly higher at the time of peak symptoms compared with either samples obtained 4 weeks after symptom resolution from the same subjects or levels in nasal secretions of healthy asymptomatic subjects. These data contrast with those of De Silva et al, 28 who found no significant increase in VEGF protein levels in nasal aspirates from patients with confirmed HRV infections compared with noninfected control subjects but agree with the findings of a significant increase in VEGF protein levels in nasopharyngeal secretions of 9 children during asthma exacerbations associated with the presence of HRV compared with levels in the same subjects at baseline. 27 We extended these observations by demonstrating that the levels of VEGF in nasal secretions correlate with viral peak viral titers (r 5 0.35, P 5 .03) and with IP-10 protein levels (r 5 0.70, P < .001).…”
Section: Discussioncontrasting
confidence: 78%
“…Recently, Wark et al have shown that IFN-γ-induced protein 10 (IP-10) is released from bronchial epithelial cells (BECs) after RV infection, suggesting that it could be used as a specific marker to predict virus-induced asthma exacerbations [103]. RV infection induces the production of VEGF, the major mediator of angiogenesis, in primary airway epithelial cells and fibroblasts, which may be associated with airway modeling and asthma persistence [104106]. …”
Section: Role Of Infections In Airway Allergic Inflammation Of Asthmamentioning
confidence: 99%
“…22 The mechanisms through which HRV leads to altered airway function associated with exacerbations is not known for certain, but in addition to the enhanced cell cytotoxicity observed in asthmatic epithelial cells, 18 infection with HRV induces mucin production, 23 delays epithelial repair, 24 induces cytokine and chemokine release to recruit secondary effector cells, 25 and promotes the production of growth factors. 26 The inability of the asthmatic airway epithelium to effectively defend the lung against what is normally an innocuous virus raises the possibility of this being part of a broader epithelial defect relevant to asthma pathogenesis. The recent discovery of filaggrin as a key molecule involved in maintaining epithelial integrity and its dysfunction in atopic dermatitis and asthma 27 adds support to the view that diseases such as eczema and asthma are disorders of the epithelium rather than primarily being diseases of the adaptive immune response.…”
mentioning
confidence: 99%